Using Community Composition and Successional Theory to Guide Site‐Specific Coral Reef Management - Orion S. McCarthy; Emily L. A. Kelly; Anela K. Akiona; Samantha M. Clements; Tatiana Martinez; Nicole E. Pedersen; Cole Peralto; Sarah L. Romero; Mitchell H. Smelser; Kristy Wong Stone; Russell T. Sparks; Jennifer E. Smith (Global Change Biology, 2025)
High spatial or temporal variability in community composition makes it challenging for natural resource managers to predict ecosystem trajectories at scales relevant to management. This is commonly the case in nearshore marine environments, where the frequency and intensity of disturbance events vary at the sub‐kilometer to meter scale, creating a patchwork of successional stages within a single ecosystem. The successional stage of a community impacts its stability, recovery potential, and trajectory over time in predictable ways. Here we demonstrate the value of successional theory for interpreting fine‐scale community heterogeneity using Hawaiian coral reefs as a case study. We tracked benthic community dynamics on 36 forereefs over a 6‐year period (2017–2023) that captures impacts from high surf events, a marine heatwave, and unprecedented shifts in human behavior due to the COVID‐19 pandemic. We document high spatial variation in benthic community composition that was only partially explained by island and environmental regime. Through hierarchical clustering, we identify three distinct community types that appear to represent different successional stages of reef development. Reefs belonging to the same community type exhibited similar rates of change in coral cover and structural complexity over time, more so than reefs located on the same island. Importantly, communities that were indicative of early succession (low coral cover reefs dominated by stress‐tolerant corals) were most likely to experience an increase in coral cover over time, while later‐stage successional communities were more likely to experience coral decline. Our findings highlight the influence of life history and successional stage on community trajectories. Accounting for these factors, not simply overall coral cover, is essential for designing effective management interventions. Site‐specific management that accounts for a community's unique composition and history of disturbance is needed to effectively conserve these important ecosystems.